High Sensitivity of Diffusion-weighted MR Imaging for the Detection of Liver Metastases from Neuroendocrine Tumors: Comparison with T2-weighted and Dynamic Gadolinium-enhanced MR Imaging - d’Assignies, Gaspard; Fina, Priscilla; Bruno, Onorina; Vullierme, Marie-Pierre; Tubach, Florence; Paradis, Valérie; Sauvanet, Alain; Ruszniewski, Philippe; Vilgrain, Valérie (Radiology, 2013)
To compare the sensitivity and specificity of diffusion-weighted (DW) magnetic resonance (MR) imaging for identifying liver metastases from neuroendocrine tumor (NET) to those of T2-weighted fast spin-echo (FSE) and three-dimensional dynamic gadolinium-enhanced MR imaging, with surgical and histopathologic findings as the reference standard. This retrospective study was approved by institutional review board, and informed consent was waived. Fifty-nine patients with NETs (41 patients with 162 liver metastases, and 18 control subjects with no liver metastases) underwent MR imaging that included DW, T2-weighted FSE, and dynamic gadolinium-enhanced MR sequences. Images were retrospectively reviewed by two abdominal radiologists, independently, for the detection and characterization of liver metastases. MR findings were compared with histopathologic and intraoperative ultrasonography findings for metastasis on a lesion-by-lesion basis to determine the sensitivity of each MR sequence alone and combined. Specificity was calculated by using the control population. Interreader agreement for each MR sequence and McNemar test were also calculated. There was excellent agreement between observers 1 and 2 for characterizing liver metastases at per-lesion analysis (κ coefficient: 0.86-1.00). DW MR was more sensitive (observer 1: sensitivity, 71.6% [116 of 162], 95% confidence interval [CI]: 64.2%, 78.0%; observer 2: sensitivity, 71.0% [115 of 162], 95% CI: 63.6%, 77.4%) than T2-weighted FSE (observer 1: sensitivity, 55.6% [90 of 162], 95% CI: 47.9%, 63.0%; observer 2: sensitivity, 55.6% [90 of 162], 95% CI: 47.9%, 63.0%) and dynamic gadolinium-enhanced MR (observer 1: sensitivity, 47.5% [77 of 162], 95% CI: 34.0%, 55.2%; observer 2: sensitivity, 48.1% [78 of 162], 95% CI: 40.6%, 55.8%) (P < .001 for both, McNemar test). The specificity of these sequences ranged from 88.9% to 100% (DW MR vs T2-weighted FSE MR: P > .99, DW MR vs dynamic gadolinium-enhanced MR: P = .61, and T2-weighted FSE MR vs dynamic gadolinium-enhanced MR: P = .61, McNemar test). DW MR imaging was more sensitive for the detection and characterization of liver metastases from NETs than T2-weighted FSE and dynamic gadolinium-enhanced MR imaging and should be systematically performed.